Transcriptome Profiling Reveals Differential Gene Expression of Secreted Proteases and Highly Specific Gene Repertoires Involved in Lactarius–Pinus Symbioses - Tang, Nianwu; Lebreton, Annie; Xu, Wenjun; Dai, Yucheng; Yu, Fuqiang; Martin, Francis M. (Frontiers in Plant Science, 2021)
Ectomycorrhizal fungi establish a mutualistic symbiosis in roots of most woody plants. The molecular underpinning of ectomycorrhizal development was only explored in a few lineages. Here, we characterized the symbiotic transcriptomes of several milkcap species (Lactarius, Russulales) in association with different pine hosts. A time-course study of changes in gene expression during the development of L. deliciosus-Pinus taeda symbiosis identified six to 594 differentially expressed fungal genes at various developmental stages. Up- or down-regulation of genes are involved in signaling pathways, nutrient transport, cell wall modifications and plant defenses. A high number of genes coding for secreted proteases, especially sedolisins, were induced during root colonization. In contrast, only a few genes encoding mycorrhiza-induced small secreted proteins were identified. This feature was confirmed in several other Lactarius species in association with various pines. Further comparison among all these species revealed that each Lactarius species encodes a highly specific symbiotic gene repertoire, a feature possibly related to their host-specificity. This study provides insights on the genetic basis of symbiosis in an ectomycorrhizal order, the Russulales, which was not investigated so far.